Breeding rice for heat tolerance and climate change scenario; possibilities and way forward. A review. Issue 1 (2nd January 2022) - Senguttuvel, Ponnuvel; Jaldhani, Veerendra; Raju, Nannapu Sravan; Balakrishnan, Divya; Beulah, Pasumarthi; Bhadana, Vijai Pal; Mangrauthia, Satendra Kumar; Neeraja, Chirravuri Naga; Subrahmanyam, Desiraju; Rao, Puskur Raghuveer; Hariprasad, Arramsetty Subrahmanyam; Voleti, Sitapati Rao
ABSTRACT: The consequences of climate change are drastically impacting field crop production; it is an immense prerequisite to attribute resilience through crop improvement. Thus, the breeders' task is to sustain yield potential in changing climate, which imperils the food grain security. Globally, high temperature is one of the grounds that support climate change. High temperature critically affects the sensitive stages of rice, starting from anthesis to grain filling, which dictates plant reproduction. In tropical conditions, it is often the yield-limiting factor and sources for yield penalty with poor grain quality. Exploring the ways to mitigate heat tolerance in rice resulted in identifying key traits like early morning flowering, pollen fertility, pollen shedding percentage, stigma receptivity, and spikelet fertility. Identifying germplasm resources with heat-tolerance traits is the foremost task followed by exploiting them in climate-resilient rice breeding. It prompts the breeding practices to improve tolerant varieties as an adaptation option suggested by various simulated crop models. With the advances in biotechnology, there are still more comprehensions required in connection to genetics, physiology, and molecular responses of heat tolerance. Herein, we reviewed the consequence of heat tolerance, germplasm resources, genetic and genomic mechanisms for attenuating heat stress impact of rice.